2021
DOI: 10.1007/s43630-021-00091-1
|View full text |Cite
|
Sign up to set email alerts
|

Solvent effect on the excited-state intramolecular double proton transfer of 1,3-bis(2-pyridylimino)-4,7-dihydroxyisoindole

Abstract: Density functional theory (DFT) and time-dependent density functional theory (TDDFT) are used to study the solvatochromic effect and the excited-state intramolecular double proton transfer (ESIDPT) of 1,3-Bis(2-pyridylimino)-4,7-dihydroxyisoindole (BPI-OH) in different kinds of solvents. The hydrogen bonding parameters and IR spectra reveal that in the excited state, the strength of excited hydrogen bond increase with the decrease of solvent polarity. Furthermore, the reduction density gradient (RDG) analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Visibly, the accumulation of electron densities around the O 3 acceptor promotes the ESIPT reaction for B‐bph‐fla‐OH system. Empirically, the energy difference between HOMO and LUMO could reflect the target molecular activity in excited state via excitation to a large extent 46–49 . Therefore, we also calculate the energy difference in five solvents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Visibly, the accumulation of electron densities around the O 3 acceptor promotes the ESIPT reaction for B‐bph‐fla‐OH system. Empirically, the energy difference between HOMO and LUMO could reflect the target molecular activity in excited state via excitation to a large extent 46–49 . Therefore, we also calculate the energy difference in five solvents.…”
Section: Resultsmentioning
confidence: 99%
“…Empirically, the energy difference between HOMO and LUMO could reflect the target molecular activity in excited state via excitation to a large extent. [46][47][48][49] Therefore, we also calculate the energy difference in five solvents. The gap is 3.704, 3.710, 3.723, 3.729, and 3.732 eV in CYC, BEN, CHL, ACE, and DMSO, respectively.…”
Section: Photo-induced Excitationmentioning
confidence: 99%
“…The explorations found that there are two types of ESIDPT, e.g., cascade and noncascade. The cascade form has been shown to undergo a stepwise transfer of two protons, whereas for the noncascade form, the mechanism is still not clear. Recently, Kumar et al synthesized an ESIDPT material hydroxyquinoline benzimidazole (HQB) with two different types of hydrogen bonds (see Scheme ). The potential energy curves calculated by using density functional theory (DFT) and time-dependent DFT (TD-DFT) methods indicate that the HQB system could undergo two proton transfers in different sequences during the deactivation pathway from the S 1 excited state back to the ground state.…”
Section: Introductionmentioning
confidence: 99%
“…The excited-state intramolecular proton-transfer (ESIPT) process was a photophysical process that induced the isomerization of intramolecular hydrogen bonds (IHBs) from enol to keto in organic molecules after photoexcitation. The presence of ESIPT resulted in a reduction of the first singlet energy level and a redshift of the emission wavelength; thus, the ESIPT molecule usually had a large Stokes shift. Molecules with ESIPT properties were considered to have potential applications in fluorescence probes, organic luminescent materials, and biomedicine. In 1950, Weller first reported the ESIPT process in methyl salicylate . Subsequently, numerous scholars were committed to exploring the molecular mechanism of the ESIPT reaction and its application value both experimentally and theoretically …”
Section: Introductionmentioning
confidence: 99%